2017
DOI: 10.1186/s13104-017-3044-4
|View full text |Cite
|
Sign up to set email alerts
|

Bivariate longitudinal data analysis: a case of hypertensive patients at Felege Hiwot Referral Hospital, Bahir Dar, Ethiopia

Abstract: ObjectiveLongitudinal data are often collected to study the evolution of biomedical markers. The study of the joint evolution of response variables concerning hypertension over time was the aim of this paper. A hospital based retrospective data were collected from September 2014 to August 2015 to identify factors that affect hypertensive. The joint mixed effect model with unstructured covariance was fitted. A total of 172 patients screened for antihypertensive drugs treated were longitudinally considered from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
14
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 24 publications
8
14
3
Order By: Relevance
“…The present study stated that average SBP and average DBP were higher for patients who had diabetes compared to patients who had no diabetic disease. Consistent with previous studies [4,27,28] the average SBP and DBP of patients who had diabetes disease were signi cantly increased compared to patients who had no diabetes disease. Which state that co-existence of diabetes mellitus and hypertension is also associated with accelerated blood pressure rising.…”
Section: Discussionsupporting
confidence: 91%
“…The present study stated that average SBP and average DBP were higher for patients who had diabetes compared to patients who had no diabetic disease. Consistent with previous studies [4,27,28] the average SBP and DBP of patients who had diabetes disease were signi cantly increased compared to patients who had no diabetes disease. Which state that co-existence of diabetes mellitus and hypertension is also associated with accelerated blood pressure rising.…”
Section: Discussionsupporting
confidence: 91%
“…Related disease is another prognostic factor that signi cantly predicts the recovery time of patients with hypertension. It showed that patients having kidney disease, other and have no related disease shortened the recovery time compared to diabetes patients; this study is supported by the study [14].…”
Section: Discussionsupporting
confidence: 80%
“…According to the results of the study conducted at Jimma University Specialized Hospital, Ethiopia, there was a high correlation between BPs evolution and the association of evolution approximates one [ 2 , 31 ]. The evolution of association between the BPs at the baseline was 0.260 and has a slight increment as time changes, this is also supported by a study FHRH, Bahir Dar, Ethiopia [ 10 ]. In the multivariate longitudinal sub-model; the observation time was negatively associated with the average SBP and DBP, that is, as the observation time increases patient’s average SBP and DBP had increased proportionately.…”
Section: Discussionsupporting
confidence: 74%
“…Following therapy modifications over time, the average systolic and diastolic blood pressure biomarkers of hypertensive patients were primarily reported [ 9 ]. A separate longitudinal study conducted by [ 10 ] aims to assess the trends of systolic and diastolic BP over time using a bivariate linear mixed model.…”
Section: Introductionmentioning
confidence: 99%